Short-Run and Long-Run Relationship Between Indonesia's Export Value and Real Gross Domestic Product: Quarterly Data Analysis 2010Q1–2026Q1 - Noldin Jerry Tumbel (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study examines the short-run and long-run relationship between export value and Indonesia’s real gross domestic product (GDP) to evaluate the validity of the export-led growth hypothesis. Research Method: The study uses 65 quarterly observations from 2010 to 2026, consisting of real GDP at constant 2010 prices and export value. The Autoregressive Distributed Lag (ARDL) approach, bounds test for cointegration, unit root test, and diagnostic and stability tests were employed to examine the relationship between the variables. Results and Discussion: The unit root results indicate that both variables are integrated of order one, I(1). Based on the Bayesian Information Criterion, the ARDL (1,1) model was selected as the optimal specification. The bounds test produced an F-statistic of 0.874, which is below the 5% lower critical bound, indicating no long-run cointegrating relationship between export value and real GDP. Although changes in export value have a positive and statistically significant short-run effect, the model exhibits heteroskedasticity, non-normal residuals, and parameter instability, particularly during the economic shock in the second quarter of 2020. These findings suggest that higher export values alone do not guarantee sustained economic growth because their impact depends on export composition, domestic value added, import content, and broader macroeconomic conditions. Implications: Policies should emphasize export diversification and higher domestic value-added production rather than focusing solely on increasing export value. Originality: This study provides updated evidence on Indonesia’s export-led growth hypothesis using quarterly data through 2026 and demonstrates the absence of a stable long-run relationship despite significant short-run effects.